2005
DOI: 10.1097/00019501-200502000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma soluble adhesion molecules; intercellular adhesion molecule-1, vascular cell adhesion molecule-1 and E-selectin levels in patients with isolated coronary artery ectasia

Abstract: We have shown that patients with isolated CAE have raised levels of plasma soluble ICAM-1, VCAM-1 and E-selectin in comparison with patients with obstructive CAD without CAE and control subjects with normal coronary arteries, suggesting the presence of a more severe and extensive chronic inflammation in the coronary circulation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 23 publications
3
79
1
1
Order By: Relevance
“…16 Systemic hypertension; inflammatory stimuli such as tobacco; hyperhomocysteinemia; acceleration of the atherosclerotic process and/or interference with the normal cross-linking of collagen and chronic EpsteinBarr virus infection; genetic factors including HLA-DR B1* 13, DR16, DQ2, and DQ5, and MMP-3 and MMP-3 gene (MMP-3 5A allele) disruption, and insertion/deletion polymorphism of angiotensin-converting enzyme (ACE DD genotype); increased inflammatory response in the vessel wall; and activation of matrix metalloproteinases are possible factors in the vessel-wall weakening that induces CAE. 2,12,[17][18][19][20]21 Extensive vascular wall inflammation, involving all layers of the vascular wall, plays a major role in the development of CAE.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…16 Systemic hypertension; inflammatory stimuli such as tobacco; hyperhomocysteinemia; acceleration of the atherosclerotic process and/or interference with the normal cross-linking of collagen and chronic EpsteinBarr virus infection; genetic factors including HLA-DR B1* 13, DR16, DQ2, and DQ5, and MMP-3 and MMP-3 gene (MMP-3 5A allele) disruption, and insertion/deletion polymorphism of angiotensin-converting enzyme (ACE DD genotype); increased inflammatory response in the vessel wall; and activation of matrix metalloproteinases are possible factors in the vessel-wall weakening that induces CAE. 2,12,[17][18][19][20]21 Extensive vascular wall inflammation, involving all layers of the vascular wall, plays a major role in the development of CAE.…”
Section: Pathogenesismentioning
confidence: 99%
“…2,12,[17][18][19][20]21 Extensive vascular wall inflammation, involving all layers of the vascular wall, plays a major role in the development of CAE. 16 Soluble adhesion molecules including vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and E-selectin, which are expressed on vascular endothelium and on immune and inflammatory cells and mediate the adhesion and transmigration of leukocytes to vascular endothelium, are increased in sera of patients with CAE. 16 Factors that may contribute to the pathogenesis of aneurysms are matrix-degrading enzymes such as collagenases, gelatinases, and stromelysins.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we have focused on the role played by inflammation in the genesis of the aneurysmal process, as suggested in several studies in literature [21,[27][28][29][30]. Specifically, we measured in all patients the serum levels of C-reactive protein and we found that its values were higher in patients with CAE compared with those who had normal coronary arteries; furthermore there was an increase in CRP values in direct proportion to the number of vessels involved from ectasia, thus confirming the hypothesis that the degree of inflammation is higher in patients with diffuse ectasia compared to the focal ectasia.…”
Section: Discussion:-mentioning
confidence: 99%
“…Higher levels of local metalloproteinase and plasma soluble adhesion molecules such as ICAM-1, VCAM-1, and E-selectin are also observed in CAE patients (7,8). Moreover, varicose veins and varicocele are significantly higher in this condition, which may suggest the possible existence of a generalized defect in the vascular wall (9).…”
Section: Introductionmentioning
confidence: 85%